To what extent are the Christian clergy acting as frontline mental health workers? A study from the North of England - Wood, Emily (Mental health, religion & culture, 2011)
The Church has always been associated with care of the sick; this continues today many clergy see people with mental health issues. Studies outside the United Kingdom have shown that when people with mental health issues visit clergy for help they often do this before, or instead of, seeing health professionals. This study surveyed Christian clergy and asked about the frequency with which clergy saw people with mental health problems, if they referred onto healthcare professionals, what outcomes they expected and their attitudes to mental health. It was concluded that the clergy did see people with mental health problems but the frequency varied amongst individuals and this was not dependent on denomination. These findings agreed with other studies that a very high percentage of British clergy do refer on, unlike North American clergy and this was not related to denomination.